2020
DOI: 10.3390/su12145607
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Political Connection and Information Asymmetry on Investment Efficiency: Evidence from China

Abstract: This study investigates the impact of political connection and information asymmetry on the investment efficiency of firms in China. This paper employs a panel data regression analysis on a dataset comprising 4307 observations for listed companies from 2008 to 2015. The results indicate that if taken alone, neither political connection nor information asymmetry affects firms’ investment efficiency. However, the interactive effect of both political connection and information asymmetry significantly reduces firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…The economic consequences of political connections are determined not only by motivation, but also by input costs. The so-called motive decision means that SOEs are subject to policy favoritism due to government intervention and may achieve more social goals [27,28], while private enterprises use political connections to win government attention, such as financing concessions [29][30][31][32][33][34], tax concessions [35], and government subsidies [36,37]. The so-called "cost-affected" refers to the private enterprise's investment in political connections under resource-constrained conditions, which will result in insufficient investment in core capacity building, and have a long-run negative impact on the organization, incentive mechanism and cultural construction of the enterprise [15].…”
Section: Institutional Background Theoretical Analysis and Hypothesismentioning
confidence: 99%
“…The economic consequences of political connections are determined not only by motivation, but also by input costs. The so-called motive decision means that SOEs are subject to policy favoritism due to government intervention and may achieve more social goals [27,28], while private enterprises use political connections to win government attention, such as financing concessions [29][30][31][32][33][34], tax concessions [35], and government subsidies [36,37]. The so-called "cost-affected" refers to the private enterprise's investment in political connections under resource-constrained conditions, which will result in insufficient investment in core capacity building, and have a long-run negative impact on the organization, incentive mechanism and cultural construction of the enterprise [15].…”
Section: Institutional Background Theoretical Analysis and Hypothesismentioning
confidence: 99%
“…The results show; that business strategy plays an important role in shaping investment behavior and efficiency. Yu et al (2020) found that political relevance and information asymmetry affect corporate investment efficiency. Shin et al (2020), showed that there is a positive relationship between women managers and investment efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ratio of total liabilities to total assets at the end of the fiscal year is used to calculate financial leverage (Yu et al, 2020).…”
Section: Financial Leverage ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…For individual investors in China, there are various ways to acquire market information, including internet search engine(s), institutional databases, professional websites, exhibitions, other investors either personally known or online, market exploration, conferences, and forums. Actual market information is raw data that financial services companies typically gather, process, and sell, or provide it to their clientele [40].…”
Section: Market Information Acquisitionmentioning
confidence: 99%